Investigation of the Effect of Duct Geometry on Drying Air Flow in Conventional Grain Dryers by Porous Media Approach - Danışmaz, Merdin (Fırat University, 2024)
It is a traditional practice to store many agricultural products after drying, ensuring that they are used all year round. Mixed counter flow air drying is one of the most common and traditional methods in the bulk drying process. In this application, the air flow produced by the air channels placed in the dryer bed is forced to flow through the grains in the opposite direction to the grain flow. The moisture contained in the grains is thrown out of the dryer through forced convection. However, it is expected that the air ducts installed in the dryers should not obstruct the flow of grain and provide the best possible drying performance. In this study, computational fluid dynamics (CFD) modeling for a counter-flow grain dryer was performed and the effect of the geometry of the drying channels on the process was investigated. Fluent 2020 R2 commercial software was used for 2-D flow modeling through the dryer. The airflow in the grain zone, modeled as porous media, was included in the calculation for three different geometries of the dryer air ducts (circular, angular, and straight). A constant temperature boundary condition (37°C) was applied for the air ducts in which the drying air circulated without mixing with the grain. As an output of the analysis, the dryer outlet temperature and differential pressure variation along the flow were calculated for 5 different inlet velocities (between 0.005-0.25) to determine the behavior of different air flow rates in the drying process. The increase in the inlet velocity increased the pressure difference and consequently the stability of the flow for all models. The outlet temperature decreased by about 2.5 °C with a 5-fold increase in velocity. The results showed that the sufficient outlet air for moisture removal depends on the structure of the porous medium and the flow geometry. For this analysis, the best flow was found to be for the circular cross-section model and the outlet temperature could be at acceptable levels.

Pek çok tarım ürünün kurutulduktan sonra depolanması geleneksel bir uygulamadır ve bu şekilde yıl boyu kullanılması sağlanır. Hasadı yapılan tahılın depolama ömrünün artırılması için nem içeriğinin kabul edilebilir seviyelere (genellikle
Geleneksel Tahıl Kurutuculardaki Kanal Geometrisinin Kurutma Havası Akışına Etkisinin Gözenekli Ortam Yaklaşımıyla İncelenmesi
Keywords: Fluid Mechanics and Thermal Engineering (Other); Akışkan Mekaniği ve Termal Mühendislik (Diğer); Numerical Methods in Mechanical Engineering; Makine Mühendisliğinde Sayısal Yöntemler